1989
DOI: 10.2176/nmc.29.772
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Nerve Deafness due to Rupture of a Right Vertebral Artery Aneurysm

Abstract: A 49-year-old female with no history of hearing disturbance developed sudden onset of headache and was admitted with no neurological deficits other than mild nuchal rigidity. Computed tomography (CT) showed subarachnoid hemorrhage. Four-vessel cerebral angiography disclosed no aneurysm. A second angiogram obtained on the 14th day showed vasospasm of the bilateral posterior cerebral arteries and right anterior inferior cerebellar artery, but still failed to demonstrate an aneurysm. Following the second angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Our results in four of five cases also suggest a high probability of "angiographic cure" (which includes occlusion of the affected vessel) in this disease. It is noteworthy that, in Case 4 of the present series and in the cases of Friedman and Drake, 9 Ito,et al,13 and Nishizawa,et al,19 follow-up angiography revealed definite signs of arterial dissection that were not present on the admission angiography. The angiographic changes occurred without apparent clinical deterioration, except in the case of Nishizawa, et al (Case 10, Table 4).…”
Section: Serial Angiographic Studysupporting
confidence: 44%
See 1 more Smart Citation
“…Our results in four of five cases also suggest a high probability of "angiographic cure" (which includes occlusion of the affected vessel) in this disease. It is noteworthy that, in Case 4 of the present series and in the cases of Friedman and Drake, 9 Ito,et al,13 and Nishizawa,et al,19 follow-up angiography revealed definite signs of arterial dissection that were not present on the admission angiography. The angiographic changes occurred without apparent clinical deterioration, except in the case of Nishizawa, et al (Case 10, Table 4).…”
Section: Serial Angiographic Studysupporting
confidence: 44%
“…Our review of the relevant literature revealed 12 cases of intracranial vertebral artery dissection in which serial angiographies were available (Table 4). 2,6,[9][10][11]13,19,26 Among the 12 cases, only two showed no interval changes on serial angiography.5,10…”
Section: Serial Angiographic Studymentioning
confidence: 99%
“…Hence, cortical deafness in this patient was caused by vasospasm contralateral to the previous infarction. Unilateral deafness that occurred after the rupture of a right vertebral artery dissecting aneurysm resulted from ischemia in the territory of the right internal auditory artery due to vasospasm [52]. …”
Section: Reviewmentioning
confidence: 99%
“…It results from damage to both temporal or temporoparietal lobes including the primary auditory cortex (Broadmann areas 41 and 42) on both transverse gyri (Heschl). [4] [2] 21/F Bilateral ND Subarachnoid bleed affecting both inferior colliculi Tabuchi et al(2007) [1] 61/F Bilateral Right ICA Cotical due to MCA spasm Maslehaty et al(2010) [2] 59/M Bilateral ACOM Cotical due to MCA spasm Ponzetti et al (2013) [3] 55 [4] 49/F Unilateral Intrameatal AICA Mass effect Hori et al (1971) [4] 35/F Unilateral Intrameatal AICA Mass effect Arnold et al (1977) [5] 68/F Unilateral Basilar artery Infiltration of internal auditory canal by erythrocytes Conclasure et al (1981) [6] Bilateral PCOM artery ND Kamano et al (1986) [4] 58/F Unilateral Intrameatal AICA Mass effect Inoue et al (1987) [4] 43/F Intrameatal AICA Mass effect Nishizawa et al (1989) [7] 49/F Unilateral Vertebral artery Spasm of internal auditory artery Gleeson et al (1989) [4] 57/F Unilateral Intrameatal AICA Mass effect Kiya et al (1989) [4] 64/F Unilateral Intrameatal AICA Mass effect Spallone et al (1995) [4] 46/F Unilateral Intrameatal AICA Mass effect Banczerowski et al (1996) [2] -Unilateral AICA-IAA junction Mass effect Okumura et al (1998) [2] 77/F Unilateral Intrameatal AICA Mass effect Zager et al (2002) [2] 37/M Unilateral Intrameatal AICA Mass effect Tokumitsu et al (2004) [2] 59/F Unilateral Intrameatal AICA Mass effect M -Male, F -Female, ND -Not described, PCOM -Posterior communicating artery, AICA -Anterio-inferior cerebellar artery, IAA -Intenal auditory artery [1] Different causes of cortical deafness include congenital lesions, cerebral infarction or cerebral hemorrhage.…”
Section: Vasospasm Causing Reversible Cortical Deafness In Subarachnomentioning
confidence: 99%